Wartości w teorii prawa Jerzego Wróblewskiego - Leszczyński, Jerzy (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The article presents the role of values and evaluation practices in Jerzy Wróblewski`s legal theory. An overview of the theory includes here the interpretation and the application of the law, in both of which Wróblewski shows the axiological choices made by a lawyer. These choices are only partly limited by the interpretative directives, those generally accepted in a legal culture. The author of the article describes the two ideologies (normative theories), distinguished by Wroblewski, of the legal interpretation (and of the application of the law), which are contradictory to each other as they refer to opposing values: legal certainty and flexibility of law. A third type of ideology, identified by Wróblewski refers to the value of rationality and tries to mitigate the contradictions of the previous two. Some similarities between Wróblewski`s legal theory and the theory of H.L.A.Hart may allow to treat him as the co-founder of a sophisticated version of legal positivism.